Spatio-temporal distribution of planktonic cyanobacteria and environmental factors associated with their proliferation in the Cerrón Grande reservoir, El Salvador - Ortez, Luis (2022)
Introduction: The 135 km2 Cerrón Grande reservoir is the largest wetland in El Salvador, recognized as "Wetland of International Importance" by the Ramsar Convention. It is also one of the most polluted ecosystems nationwide, facing serious problems, among them, a proliferation of cyanobacteria. Objective: To assess the relationships among environmental factors and the spatial and temporary distribution of cyanobacteria in the reservoir throughout a hydrological year. Methods: We extracted water with cyanobacteria from six fixed sites, from October 2018 through September 2019. Results: We identified 16 genera, the most abundant Microcystis sp. And Dolichospermum sp.; Microcystis sp. reached 1.5 x 106 cells/ml in June 2019, mainly in the north-west sector, which is shallow and close to the confluence zones where highly polluted tributaries reach the reservoir. The deeper south-east sector had low concentrations of these organisms. The environmental factors mostly related to this behavior were: phosphorus, electrical conductivity and Secchi value, as expected from a eutrophic body. Conclusions: Variation in the cellular concentration of cyanobacteria in this reservoir is highly influenced by rain, water mixing and nutrient content.